Vascular mimicry: A potential therapeutic target in breast cancer - Chavoshi, Hadi; Poormolaie, Neda; Vahedian, Vahid [UNESP]; Kazemzadeh, Hamid; Mir, Amirabbas; Nejabati, Hamid Reza; Behroozi, Javad; Isazadeh, Alireza; Hajezimian, Saba; Nouri, Mohammad; Maroufi, Nazila Fathi (Elsevier, 2022)
Treating breast cancer, especially in the invasive state, is one of the challenges in treating cancer. Invasion and metastasis are factors in the failure of breast cancer treatments. One of the causes of this failure is the formation of new blood vessels to nourish the tumor cells. Although many drugs target the formation of blood vessels, the therapeutic results, especially in breast cancer, have not been very successful and even recurrence of the disease has been observed. Therefore, it can be concluded that other mechanisms are involved in feeding and delivering oxygen to tumor cells, the most important of which is the vascular mimicry (VM). The ability of cancer cells to organize themselves into vascular-like structures for the obtain of nutrients and oxygen independently of normal blood vessels or angiogenesis named Vasculogenic mimicry. In this review article, we tried to review the formation VM and the therapeutic potential of targeting VM formation in the treatment of breast cancer.
Keywords: Angiogenesis; Breast cancer; Metastasis; Therapeutic Target; VM